Pre-infectional anatomical characteristics In cluster bean leaf in relation to Alternaria blight resistance - and P.P. GUPTA1, M.S. SAHARAN, G.S. SAHARAN1 (Indian Phytopathology, 2002)
Stomatal (frequency, size & index) and epidermal hairs (number & size) were compared on two moderately resistant (HG-75, HG-365), four susceptible (HG-258, HFG-1l9, RGC-936 and RGC-IOI7) and one highly susceptible (FS277) genotypes of cluster bean to Alternaria blight disease caused by Alternaria cucumerina var. cyamopsidis. The stomatal frequency, size and stomatal index on both leaf surfaces did not differ significantly in moderately resistant, susceptible and highly susceptible genotypes. On adaxial leaf surface, the number of hairs ranged from 23 to 25 in moderately resistant genotypes while in susceptible and highly susceptible genotypes, hair number ranged from I3 to 17. While on abaxial leaf surface, there were no significant differences in hair numbers and size in moderately resistant, susceptible and highly susceptible genotypes. With the ad~ancement of crop age, wax content decreased in all the genotypes. There was higher wax content in moderately resistant genotypes at all stages of crop growth (50, 65 and 80 OAS) as compared to susceptible genotypes but differences were not significant statistically. Thus anatomical characters viz., stomatal (frequency, size& index), hairs (number & size) and wax amount do not have any relationship with Alternaria blight resistance in c1usterbean genotypes.